مـــــبدأ حســـن النية في إبـــــرام العقـود - موسى شلالي - المبروك مقيرش (My University, 2022)
يعتبر مبدأ حسن النية من القواعد الأخلاقية التي فرضت نفسها كقاعدة قانونية، لما له من دور في جميع مراحل العقد، خاصة في المرحلة السابقة للتعاقد، ومرحلة الإبرام، وذلك من خلال المحافظة على المراكز القانونية وديمومة العقود، خاصة بعد التطور الذي شهده المجال الاقتصادي والتكنولوجي، الذي انعكس على العلاقات العقدية، أين تكون مرحلة التفاوض هي أساس إنجاح إبرام العقد المنشود، إلاّ أننا نجد أنّ بعض التشريعات أقرّت تطبيق مبدأ حسن النية على مرحلة تنفيذ العقد فقط، ومنها التشريع الجزائري، في المقابل هناك تشريعات فرضته في جميع مراحل العقد، كالتشريع الفرنسي بعد تعديل القانون المدني سنة 2016. فمبدأ حسن النية يفرض عدة التزامات على المتفاوضين، حماية للرضا واستقرار التعاملات، وتحقيق العدالة، كما أنّ الإخلال بهذه الالتزامات توجب المسؤولية المدنية على من يخلّ بها، والتي بدورها تُوقِعُ جزاءً جرّاء مخالفة تلك الالتزامات، أين يستبعدُ فيها التنفيذ العيني حسب أغلب الفقهاء، ويظل التنفيذ بمقابل أو عن طريق التعويض هو الجزاء الملائم. Abstract: The principal of good faith is considered as one of the ethical rules that imposed itself as a legal rule, and that returns to its role in all phases of the contract, especially in the pre-contract phase, and conclusion of the contract, through the preservation of the perpetuity of contracts, particularly after the evolution witnessed in both economy and technology fields, which was reflected in the contractual relations, where the negotiation phase is the basis to reach the desired contract and make the deal, however, we find that some legislations has approved the application of good faith principal only on the execution phase of the contract, including the Algerian legislation, on the other hand, there are legislations that has enforced it at all phases of the contract, such as the French legislation after the amendment of civil code in 2016. The principle of good faith imposes several obligations on negotiators, in order to protect consent and stability of dealings, and to achieve justice, moreover the violation of these obligations enforces civil liability on those who violate it, which in turn inflict punishment for the violation of those obligations, where the implementation in-kind rule out according to most jurists, and remains the implementation in return or through compensation and this last is the appropriate punishment.
Keywords: مـــــبدأ -حســـن النية - إبـــــرام العقـود-القانون